HEALTH RELATED QUALITY OF LIFE ASSESSMENT INPATIENTS WITH DHS SURGICALLY TREATEDPERTROCHANTERIC KYLE FRACTURE TYPE I, II (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
Treatment of hip fractures is a major challenge to the health care system and society. Proper treatment of hip fractures in theelderly is still controversial.Objectives: To assess health-related quality of life and to demonstrate any difference following a rehabilitation treatmentwith kinesitherapy, magnetic therapy, and interferential currents.Material and methods: A quantitative analytical study of 28 patients, all females older than 65. Subjects were divided intotwo cohorts: 14 patients were treated with kinesitherapy and magnetic therapy, and 14 patients were treated withkinesitherapy and interferential currents. Standardized questionnaires, Score and Rand SF-36 with a total of 36 questionsgrouped into eight sections, were used for the health-related quality of life assessment.Results: In terms of ‘physical functioning’, the average score indicated a very poor physical functioning. The average scorefor ‘role limitations due to physical health’ indicated major role limitations due to physical health. The average score for‘role limitations due to emotional health’ indicated major role limitations due to emotional health. In terms of the ‘energy /fatigue’ parameter results indicated that patients felt a lack of energy which translated as a feeling of fatigue. The averagescore in ‘emotional wellbeing’ indicated that patients faced lack of emotional wellbeing. The ‘social functioning’ parametersuggested that patients faced problems in their social functioning. The average score in terms of ‘pain’ indicated theexistence of pain. And in terms of ‘general health’, the patients considered themselves to be in poor health.Conclusion: The results, although preliminary, indicate the importance of physical therapy in the postoperative period andits impact on the health-related quality of life, as well as the opportunity for a more efficient manner of restoring patient’scondition as it was prior to the fracture.